Variable Fall Climate Influences Nutrient Resorption and Reserve Storage in Young Peach Trees - Lawrence, Brian T.; Melgar, Juan Carlos (Frontiers in Plant Science, 2018)
A delay of leaf senescence resulting from variable fall climate may allow for additional nutrient resorption, and storage within reserve organs. Autumn leaves and reserve organs (< 1 year shoots, > 1 year shoots, stem above and below the graft union, the tap root, and fine roots) during dormancy of 2-year-old peach trees were evaluated following warmer fall temperatures and limited soil moisture on two cultivars (‘Scarletprince’ and ‘Autumnprince’ both on GuardianTM rootstock) over two seasons. Four treatments were applied to the two cultivars: 1) well-watered trees (100% ETc needs) in ambient outdoor temperatures; 2) water deficient trees (50% ETc needs) in ambient outdoor temperatures; 3) well-watered trees grown within a greenhouse; and 4) water deficient trees within a greenhouse. The greenhouse environment was on average 5 °C warmer than the ambient outdoor temperature. Senescence was delayed on greenhouse-grown trees both years with leaf number and area similar in the greenhouse and outdoor environments prior to senescence. Across leaf samples, leaf nitrogen and phosphorus concentrations were lower within delayed senescence tree leaves while potassium was lower in leaves experiencing normal senescence. During dormancy, multiple reserve organs showed higher nitrogen, phosphorus and potassium in trees with delayed senescence than normal senescence and similar increases were observed in water-deficient trees compared to well-watered trees. Phosphorus and potassium concentrations were also higher in multiple reserve organs within ‘Autumnprince’ trees compared to ‘Scarletprince’ trees. This study suggests variable climate conditions of increased temperatures or reduced soil moisture during autumn resulting in delayed senescence influence the process of nutrient resorption and increase nutrient storage within reserve organs.